Developing English Printed Material on Theme of Myself for Early Young Learners at PAUD Terpadu Joy Kids Makassar: Developing English Printed Material - Khatima, Khusnul (Journal of Islamic Culture and Literature (JICeL), 2023)
This study was set to develop thematic English material for early young learners at PAUD Terpadu Joy Kids Makassar which focused on the theme “Myself” and specifically into the sub of theme “The Five Senses”. The Research and Development model implemented in this study was ADDIE (Analysis, Design, Development, Implementation, Evaluation) model which provided simple procedure to design and develop material. This study was conducted in order to provide English material for kindergarten. However, considering English is not a compulsory subject but only as an interlude subject in kindergarten and the learning material used as the reference in learning only contained one page English material. Therefore, this study presented to support early young learners in their optimal period for language acquisition by considering the curriculum used in kindergarten and inventory need of students. The data about students’ need was obtained from interview with the teacher and documents (Syllabus, Weekly Lesson Plan, Daily Lesson Plan, The existing material) analysis. Subsequently, the result of interview and observation was designed and developed as an output of this study. The product of this research was expected to be used for both teacher and students in applying English learning. in addition, this research can be helpful to be guideline in further research especially for the developing material. Keywords: English Material, Early Young Learners, Myself